The ontogeny of the porcine immune system - Sinkora, Marek; Butler, John E (Developmental and comparative immunology, 2009)
Cellular and humoral aspects of the immune response develop sequentially in the fetus. During the ontogeny, the pluripotent stem cells emerge and differentiate into all hematopoietic lineages. Basic questions including the identification of the first lympho-hematopoietic sites, the origin of T and B lymphocytes, the development of different subpopulations of alphabeta T, gammadelta T and B lymphocytes as well as development of innate immunity and the acquisition of full immunological capacities are discussed here for swine and compared with other species. The description of related topics such as fertilization, morphogenesis, maternal-fetal-neonatal physiology and early neonatal development are also discussed.
Keywords: Pregnancy; T-Lymphocytes; Maternal-Fetal Exchange; morfogeneze; Animals; Hematopoiesis; B-lymfocyty; buněčná imunita; hematopoéza; Female; Morphogenesis; embryo savčí; lymfopoéza; Immune System; Swine; hematopoetické kmenové buňky; přirozená imunita; ženské pohlaví; Lymphopoiesis; Placentation; Immunity, Cellular; maternofetální výměna látek; Hematopoietic Stem Cells; placentace; zvířata; B-Lymphocytes; prasata; imunitní systém; Embryo, Mammalian; Immunity, Innate; těhotenství; T-lymfocyty